Accuracy of abdominal circumference for diagnosing overweight in six-to-seven-years-old children (Research, Society and Development, 2022)
Objective: To estimate the accuracy of abdominal circumference measurement as a method of diagnosing overweight in six-to-seven-years-old children. Methods: A cross-sectional study involving 1026 six-to-seven-years-old schoolchildren in southern Brazil was carried out. Children’s weight and height were collected at schools. Body mass index were calculated and categorized in z-score in eutrophy, overweight and obesity. Abdominal circumference was measured in centimeters with a tape with children in standing position at midpoint between the lower ribs margin and the iliac crest. Correlation between abdominal circumference and body mass index was performed through Pearson's correlation coefficient. Sensitivity, specificity, positive and negative predictive values of abdominal circumference were estimated. The Receiver Operating Characteristic Curve was used to measure the accuracy. Results: A positive linear correlation value of 0.582 and a determination coefficient 0.39 were observed. The accuracy value of 0.859 was observed. Sensitivity, specificity, positive and negative predictive values varied according to each value in centimeters of abdominal circumference. Conclusion: Abdominal circumference measure showed to be an accurate method for detecting overweight and obesity in six-to-seven-years-old children.